1989
DOI: 10.1115/1.3240284
|View full text |Cite
|
Sign up to set email alerts
|

Component Wear in Coal-Fueled Diesel Engines

Abstract: Practical use of coal-fueled diesel engines depends on the improvement of component durability. The wear characteristics of standard materials in the coal-fueled engine were studied first. Candidate wear-resistant materials were sorted by bench-scale tests. The best material combinations were applied to small-scale engine tests for operation on seeded diesel fuel. Components with hard materials and coatings were scaled up for coal-water mixture testing on the locomotive engine. Results indicate practical solut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

1991
1991
2011
2011

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…2 (DF2). Investigations of CWM in a medium speed engine analyzing the coals and combustion products composition were performed by Flynn [10]. He carried out detailed flow tests through injectors to assess the wear rate versus various materials.…”
Section: Literature Reviewmentioning
confidence: 99%
“…2 (DF2). Investigations of CWM in a medium speed engine analyzing the coals and combustion products composition were performed by Flynn [10]. He carried out detailed flow tests through injectors to assess the wear rate versus various materials.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Most of the results presented here can be found in a series of semiannual reports [6][7][8][9][10][11] and in reference [12]. Finally, it should be pointed out that this problem--the high rate of ring and liner wear in coal-fueled diesel engines--has and continues to be addressed by GE [3]…”
mentioning
confidence: 86%
“…This seems consistent with the literature that indicates that carbon can be of concern (Yahagi (1987) and Berbezier, et al (1986) are examples of studies concerned with accelerated wear caused by soot) but tlaat the harder minerals found in the ash are the primary focus of most of the engine test research. Flynn, et al (1989) present an example of the type of wear observed in engine tests where a nitrided cylinder surface appeared polished after wearing. Aghan and Samuels (1970) suggest that this is an abrasive wear mechanism, identical to the mechanism caused by larger particles which result in much rougher surfaces, lt should be noted that adhesive wear also remains a possibility.…”
Section: Introductionmentioning
confidence: 99%
“…Having established some understanding of the wear mechanisms, the question remains of how to reduce or eliminate the accelerated wear process in a way that is economically acceptable. Typically, researchers (Kamo and Valdmanis, 1988;Prater and Courtright, 1985;Mehan, 1988;Flynn, et al, 1989) have concentrated on hardening the liners and rings, making them more resistant to the wear process. Hardening has reduced wear, but serious questions remain about the economic feasibility of the various hardening processes.…”
Section: Introductionmentioning
confidence: 99%